Collaborative Patient Centred eHealth. - De Clercq, Etienne; De Moor, Georges J. E.; Bellon, Joseph (IOS Press, 2008)
In Medical Informatics three types of processes play a central role: organizational, patient-related and decision making related processes. The first type deals with settings, such as a hospital care setting or a primary care setting; the second is related to health and disease (i.e. to patients); the third type of process aims at assisting in decision making and therapy and evolves in the brains of health care professionals. Hence, in all domains data, information and knowledge play a key role. As these three processes evolve, dealing with individuals - patients, doctors and nurses - because.